Na “beira” do cais, o centro englobador em risco: perspectivas e possibilidade de reordenamento da orla de Abaetetuba/PA - SILVA, Dalgisa da Conceição Araújo da (Universidade Federal do Pará, 2025)
This work proposes to analyze the process of transformation that has been developing along the urban riverfront of the municipality of Abaetetuba/PA, occupations in the Amazonian landscape, in areas protected by the course of tides and riparian forests in areas that should be protected. These occupations constitute areas of vulnerability, where the risks are present in the houses built in areas of water courses, in areas of erosive soil, in a caused way and without protection infrastructure, a fact that culminated in a disaster that occurred in 2014 in the São João neighborhood: a landfill collapse destroyed 13 (thirteen) houses and, as a result, 51 (fifty one) families were supported by the disaster. In a similar way, this occupation process also affected other areas of the riverside, mainly the commercial side, which I call here the encompassing center, as it is a historic neighborhood with economic and cultural potential, where one of the largest open-air fairs in the region. I followed this accident while working at the Municipal Civil Defense Coordination, and I was able to see firsthand the suffering of people who had losses of all kinds, and who were no longer able to return to their homes. This fact motivated me to question how to rearrange risk areas in already consolidated urban spaces, in order to prevent new disasters from occurring. The risk scenario takes place in Abaetetuba, in areas of different land uses and occupations, areas of social vulnerability, environmental protection, commercial flow, concentration of urban equipment and an area of historical memory. In this way, I analyze the process of transformation of the riverside neighborhoods of Abaetetuba as the formation of risk areas for the development of a proposal and planning that considers the risks and vulnerabilities present in these territories. Based on the research results, it was found that, despite the history of disasters in these places, the existing urban structure and the lack of a risk management plan that protects the riverfront contributed to the risk scenario that is presented. In this way, it is necessary to take into account the possibilities of public intervention based on improvements in existing planning instruments and the elaboration of new ones, which include the diagnosis of the areas, monitoring and a differentiated treatment for the risk areas in which the population participates. of the process. The research was carried out through data collection and application of semi-structured questionnaires with public sector agents and civil society to enable a more efficient planning proposal. The research was conceived in a multidisciplinary analysis in which contributions from municipal plans and scholars from the areas of geography, environment, social sciences and urban policy are articulated.